Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Percetakan Dodi Di Bandung - Rani Novitasari; Ramayani Yusuf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine effect of service quality and customer satisfaction of Dodi printing.This research method is descriptive with a quantitative corelation,collecting data using observation and distribution online questionnaire ,the population taken using the slovin formula, data analysis was analyzed by simple linear reference,the sample in this study amounted 88 respondents. The result showed that quality of service was classified as good in terms of indicators of reliability, responsiveness, assurance, empathy,and tangible.meanwhile,customer satisfaction was in the high category .in term of indicators of conformity of expectations Keywords: Service Quality, Customer Satisfaction